Two Wheeler Helmets with Ventilation and Metal Foam - Pinnoji, Praveen K.; Mahajan, Puneet (Defence Science Journal, 2008)
Three different two wheeler helmets were studied to investigate their dynamic performance.First is helmet with ABS shell, second is helmet with metal foam, and third is helmet with singlegroove in the liner foam for providing ventilation. Front and side impact analyses were carriedout at 10 m/s velocity by using LS-DYNATM. Forces on the helmet and on the head due to impactwere studied with function of time. Pressure and stresses in the brain were investigated andfound not to change significantly due to the presence of groove in the liner foam, which wasprovided to improve the ventilation in helmets. The dynamic performance of a helmet with outershell as metal foam was examined and compared with ABS material.